The area of discovery of Apanteles glomeratus (Hymenoptera: Braconidae),Pteromalus puparum (Pteromalidae) and Brachymeria regina (Chalcididae) - Syed Hassan, Syed Tajuddin (Wiley, 1976)
The areas of discovery of Apanteles glomeratus, Pteromalus puparum and Brachymeria regina were calculated using two different models. Increasing host or parasite density generally resulted in an initial increase followed by a decrease in area of discovery.